2019
DOI: 10.24911/sjp.106-1573461977
|View full text |Cite
|
Sign up to set email alerts
|

Radiological study of anatomical bony arrangement of the clubfoot deformity and its correlation with the Pirani clinical scoring system: A multicenter study

Abstract: Club foot or congenital talipes equinovarus (CTEV) is a common developmental disorder of the foot, affecting 1 per 1,000 live births. The main goal of this study is to evaluate the anatomical bony arrangement of the clubfoot deformity radiologically and to correlate this arrangement with the Pirani clinical scoring system. This descriptive, analytical study was conducted in three centres in Sudan. It recruited all the patients of both sexes with CTEV attending these centres, and excluding children on conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, since it is a simple and well tolerated procedure, it would not preclude other types of treatment once rebound occurs. Meanwhile, although previous studies have shown that the talo‐first metatarsal angle used to describe the forefoot adduction correlated significantly with the clinical score of Pirani clinical scoring system 26 , there was no preoperative or postoperative evaluation of foot function. In subsequent studies, it is necessary to increase the sample size, extend the follow‐up time and develop a more perfect evaluation system.…”
Section: Discussionmentioning
confidence: 97%
“…However, since it is a simple and well tolerated procedure, it would not preclude other types of treatment once rebound occurs. Meanwhile, although previous studies have shown that the talo‐first metatarsal angle used to describe the forefoot adduction correlated significantly with the clinical score of Pirani clinical scoring system 26 , there was no preoperative or postoperative evaluation of foot function. In subsequent studies, it is necessary to increase the sample size, extend the follow‐up time and develop a more perfect evaluation system.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, we investigated the predictive value of five angles: TC-AP, TM-AP, TC-L, TIC-L, and TM-L. 13 , 28 In particular, as shown by previous studies, the TM-AP angle can assess the severity of forefoot adduction; the TC-AP and TC-L angles can evaluate the position of the subtalar joint; the TM-L angle can estimate the severity of the midfoot cavus; and the TIC-L angle can evaluate ankle dorsiflexion. 13 , 28 , 29 As a result, these five angular measurements summarize all the IC deformity components. 3 , 7 According to our data, although TC-AP, TM-AP, TC-L, and TIC-L were significantly different between the non-relapsed and relapsed groups, TC-AP (p = 0.57) and TC-L (p = 0.19) had to be excluded because their p-value was >0.05, while only TM-AP (p = 0.033) and TIC-L (p = 0.015) could be included in the predictive formula using the stepwise selection method.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some authors reported the involvement of lower limbs genetic mechanisms and possible influence on the development of tarsal bones [5]. Radiographic and sonographic studies on the development of tarsal bone shape in treated clubfeet revealed marked differences from normal feet but observed also some methodological difficulty in detecting morphological differences with these imaging modalities [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%